2020
DOI: 10.1051/e3sconf/202019301065
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence for classification of tomato fruits by their maturity stage

Abstract: Classification of tomato fruit and control of post-harvest maturation based on the stage of maturity at harvesting, are necessary to ensure the highest possible quality and marketability of the final ripe product. A method of sorting tomatoes to assess the degree of their maturation based on the control of their chlorophyll fluorescence induction is proposed. Tomatoes (Black baron) at five different stages of maturity were used. Variance analysis (ANOVA) was performed and the Duncan’s mean values were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…All the operations occur in the competition; therefore, an increase or decrease in one pathway affects the intensity of others. Moreover, estimation of the total yield of fluorescence (chlorophyll) can provide information about changes in the power of photochemistry and heat generation ( Figure 3(a) ) [ 124 , 125 ].…”
Section: Non-destructive Techniques and Food Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…All the operations occur in the competition; therefore, an increase or decrease in one pathway affects the intensity of others. Moreover, estimation of the total yield of fluorescence (chlorophyll) can provide information about changes in the power of photochemistry and heat generation ( Figure 3(a) ) [ 124 , 125 ].…”
Section: Non-destructive Techniques and Food Quality Evaluationmentioning
confidence: 99%
“…Handheld equipment is cost-effective and readily available in the market. Numerous studies have been reported recently using CF to monitor the ripening stages of fruits, including tomato fruit [ 124 ], jujube ( Ziziphus jujuba Mill.) [ 126 ], and tobacco seeds [ 127 ].…”
Section: Non-destructive Techniques and Food Quality Evaluationmentioning
confidence: 99%
“…The process of measuring the ripeness level of tomatoes is crucial to be conducted. Measuring the ripeness level is done to separate the tomatoes that will be distributed to faraway places to prevent spoilage or for specific processing purposes (Abdelhamid et al, 2020). The maturity level of tomatoes is categorized into six maturity stages: Green stage, Breakers stage, Turning stage, Pink stage, Light Red stage, and Red stage (Choi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The chlorophyll a fluorescence technique is a valuable tool for the non-destructive analysis of physiological responses, allowing confirmation of the plant's condition in response to various environmental conditions [27,28]. In addition to diagnosing the plant's stress state based on its cultivation environment [29], recent studies have also been conducted to classify the ripening stages of tomato fruits using chlorophyll a fluorescence [30,31]. In addition to representing plant conditions through the analysis of chlorophyll a fluorescence parameters, studies are being conducted to visually express it through images [32,33].…”
Section: Introductionmentioning
confidence: 99%